Virtual machine management for Tele-Lab "IT-security" server - Ji Hu; Cordel, D.; Meinel, C. (10th IEEE Symposium on Computers and Communications (ISCC'05), 2005)
Tele-Lab "IT-security" Server is a new concept for practical security education. The Tele-lab server builds a virtual security laboratory using lightweight virtual machines and features a pure Web user interface. Thus, students can easily exercise security over the Internet. Running such a security laboratory on the Internet is difficult. Its infrastructure is subject to misuse and crash due to the nature of security tasks. The management of virtual machines is a crucial component which enables running the Tele-Lab server on the Internet. It effectively saves resources and improves security and reliability of the virtual laboratory. This paper briefly reviews the architecture of the Tele-Lab "IT-security" server, describes its virtual machine management in detail, and presents some experiential and experimental results.